Efektivitas edukasi kesehatan anemia berbasis kearifan lokal terhadap peningkatan pola konsumsi gizi pada ibu hamil - Asri Aprilia Rohman; Nina Rosdiana; Ade Sity Riyantina; Yoga Ginanjar; Irfan Permana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Anemia in pregnant women remains a major public health problem in Indonesia and contributes to adverse maternal and fetal outcomes. Inadequate dietary consumption is one of the key factors associated with maternal anemia. Local wisdom–based health education is considered a promising approach to improve dietary behavior through culturally acceptable interventions Purpose: To examine the effectiveness of local wisdom based anemia health education on improving dietary consumption patterns among pregnant women. Method: A quantitative study with a pretest–posttest control group design was conducted in November 2025 at the Rancah Community Health Center in Ciamis Regency. The sampling technique used was purposive sampling, with a sample size of 106 participants divided into an intervention group and a control group. The independent variable in this study was anemia health education based on local wisdom, while the dependent variable was improvements in nutritional intake patterns among pregnant women. Data analysis included univariate analysis in the form of frequency distributions and bivariate analysis using the Wilcoxon and Chi-Square tests. Results: The average dietary pattern score in the intervention group increased from 0.26 ± 0.44 at the pre-test to 0.68 ± 1.00 at the post-test. The control group also showed an increase, albeit a smaller one, from 0.23 ± 0.42 to 0.36 ± 0.48. Statistical analysis revealed a p-value of 0.001, indicating that health education based on local wisdom has a significant effect on improving the nutritional intake patterns of pregnant women. Conclusion: Local wisdom–based anemia health education is effective in improving dietary consumption patterns among pregnant women and should be integrated into anemia prevention programs in primary healthcare settings. Keywords: Dietary Consumption; Health Education; Local Wisdom; Maternal Anemia.